2023
DOI: 10.1021/acs.jmedchem.2c01886
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Highly Potent and BMPR2-Selective Kinase Inhibitors Using DNA-Encoded Chemical Library Screening

Abstract: The discovery of monokinase-selective inhibitors for patients is challenging because the 500+ kinases encoded by the human genome share highly conserved catalytic domains. Until now, no selective inhibitors unique for a single transforming growth factor β (TGFβ) family transmembrane receptor kinase, including bone morphogenetic protein receptor type 2 (BMPR2), have been reported. This dearth of receptor-specific kinase inhibitors hinders therapeutic options for skeletal defects and cancer as a result of an ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“… Chemical structures of BMPR-II inhibitors . The recently disclosed first-in-class BMPR2 (i.e., one of the three type II receptors) inhibitors CDD-1653 and Compound 8a feature a 2,4-diamino­pyrimidine core scaffold but are classified as distinct chemotypes based on their putatively different hinge-binding motifs. , …”
Section: Bmp Inhibitorsmentioning
confidence: 99%
“… Chemical structures of BMPR-II inhibitors . The recently disclosed first-in-class BMPR2 (i.e., one of the three type II receptors) inhibitors CDD-1653 and Compound 8a feature a 2,4-diamino­pyrimidine core scaffold but are classified as distinct chemotypes based on their putatively different hinge-binding motifs. , …”
Section: Bmp Inhibitorsmentioning
confidence: 99%
“…After capture of the magnetic beads, test compound selectivity is assessed by qPCR to quantify kinases that remain bound to the solid phase ABP. This platform has been widely used for the development of kinase inhibitors [55b,58] …”
Section: Competitive Abpp For Inhibitor Screeningmentioning
confidence: 99%
“…These compounds affect BMPR2 in the low nanomolar range, but they also showed potent inhibition of ALK1, ALK2, ALK3, TGFBR2, and VEGFR2 . More recently, Modukuri et al have identified selective benzimidazole-based potent inhibitors (CDD-1115, CDD-1653) of BMPR2 by using a DNA-encoded chemistry technology (Figure A) …”
mentioning
confidence: 99%
“…29 More recently, Modukuri et al have identified selective benzimidazole-based potent inhibitors (CDD-1115, CDD-1653) of BMPR2 by using a DNA-encoded chemistry technology (Figure 1A). 30 Compound 1 is a promiscuous kinase inhibitor developed by Statsuk et al A kinome-wide scan against 468 recombinant human protein kinases emphasized the promiscuous behavior of 1, which potently inhibits 262 kinases (Figure 1B, C). In this report, type-I and type-II BMP-receptor kinases were potently targeted.…”
mentioning
confidence: 99%
See 1 more Smart Citation